Lasting treasure : the story of George and Jennie Lonnie - Southwell, Ian ([Croydon, Victoria] : Ian Southwell, 2019)
“Lasting Treasure shares the story of George Lonnie and Jennie Hammer, who made the same great discovery: lasting treasure more precious than gold-a relationship with God through Jesus Christ. First individually, and then as a couple, they shared their discovery by proclaiming the gospel and alleviating human needs through Christian ministry in The Salvation Army in Australia and New Zealand. In so doing, they experienced precious strength to face privations, illnesses, bereavements and disappointments-as well as exciting times of great joy. The story of their resilience and courage is both challenging and inspiriring.”--Back cover.
Includes bibliographical references (pages 117-119)
Also available in electronic book form.
Keywords: Lonnie, George; Lonnie, Jennie; Salvation Army -- Australia -- Biography; Salvation Army -- New Zealand -- Biography; Salvationists -- Australia -- Biography; Australian; Biographies